1995
DOI: 10.1007/bf00172142
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid metabolites and glucocorticoid regulatory mechanism in cultured porcine tracheal smooth muscle cells

Abstract: To elucidate the signal transduction system in the production of prostaglandin E2 (PGE2) by porcine tracheal smooth muscle cells in culture (PTSMC), we examined the pattern of arachidonic acid metabolites released from PTSMC and the relationship between bradykinin-stimulated rises in intracellular calcium concentration ([Ca2+]i) and PGE2 production by PTSMC. We next examined the effect of dexamethasone on these parameters. Bradykinin induced a dose-dependent increase in both the rise in [Ca2+]i and PGE2 produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Bradykinin stimulates a rise in intracellular calcium concentration leading to PGE 2 production in cultured porcine tracheal smooth muscle cells, an effect that is suppressed by dexamethasone pretreatment for 24 h. Dexamethasone also suppressed bradykinin-stimulated release of radioactivity from cells that had been prelabeled with 3 H-arachidonic acid. These findings suggest that dexamethasone suppressed PGE 2 production by reducing the activity of cytosolic PLA 2 and PGE 2 synthase (Tanaka et al, 1995).…”
Section: Glucocorticoid Receptor-mediated Inhibition Of Arachidonic Amentioning
confidence: 75%
“…Bradykinin stimulates a rise in intracellular calcium concentration leading to PGE 2 production in cultured porcine tracheal smooth muscle cells, an effect that is suppressed by dexamethasone pretreatment for 24 h. Dexamethasone also suppressed bradykinin-stimulated release of radioactivity from cells that had been prelabeled with 3 H-arachidonic acid. These findings suggest that dexamethasone suppressed PGE 2 production by reducing the activity of cytosolic PLA 2 and PGE 2 synthase (Tanaka et al, 1995).…”
Section: Glucocorticoid Receptor-mediated Inhibition Of Arachidonic Amentioning
confidence: 75%
“…Recent studies reported that accumulation and/or hypertrophy of airway SMCs contribute to airway narrowing and airway constriction in CF patients [32,33]. A previous study showed that bradykinin-induced contraction of airway SMC occurs, in part, via a process involving a rise of [Ca 2+ ] and enhanced release of AA [34]. More recently, it has been shown that the AA metabolite 20-HETE induces sustained contraction of isolated guinea pig airway SMC [35].…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids have been reported to reduce airway constriction to various stimuli, including histamine, bradykinin and acetylcholine [58][59][60][61]. The mechanisms by which glucocorticoids reduce constriction have been investigated and include altered inositol phosphate formation and cyclic AMP levels, through receptor uncoupling or downregulation, as well as altered calcium mobilization or Na + /K + ATPase potentiation.…”
Section: Effect Of Glucocorticoidsmentioning
confidence: 98%